Sol-Gel Preparation of La Doped Strontium Titanate - Zhang, Wenjie; Sun, Xin; Yang, Bo (Asian Journal of Chemistry, 2013)
La doped strontium titanate was prepared using sol-gel method. Pure strontium titanate has larger particle size than the La doped samples. The produced substances in the samples varied in accordance to La doping content. The La doped strontium titanate might be composed of Sr2TiO4, Sr1.9La0.1TiO3.95, Sr0.8La0.2TiO3 and a small per cent of TiO2 with respect to La content. The doping of La can improve the activity of the materials when La content is between 2-7 %. The strontium titanate doped with more than 10 % La undergoes drastic activity declining. Adsorption rate of methyl orange on the two materials is not more than 3 % after 2 h. The doped strontium titanate has much improved activity than the sample without La doping. After 2 h of irradiation, methyl orange degradation rate is as high as 90.5 % on the 5 % La doped strontium titanate.